Integration of High-Performance Nanocrystalline TiO2 Photoelectrodes for N719-Sensitized Solar Cells - Ke-Jian Jiang; Jin-Ming Zhou; Kazuhiro Manseki; Qi-Sheng Liu; Jin-Hua Huang; Yan-lin Song; Shozo Yanagida (International Journal of Photoenergy)
We report on enhanced performance of N719-sensitized TiO2 solar cells (DSCs) incorporating size and photoelectron diffusion-controlled TiO2 as sensitizer-matched light-scatter layers on conventional nanocrystalline TiO2 electrodes. The double-layered N719/TiO2 composite electrode with a high dye-loading capacity exhibits the diffused reflectance of more than 50% in the range of λ = 650–800 nm, even when the films are coupled with the titania nanocrystalline underlayer in the device. As a result, the increased near-infrared light-harvesting produces a high light-to-electricity conversion efficiency of over 9% mainly due to the significant increase of Jsc. Such an optical effect of the NIR-light scattering TiO2 electrodes will be beneficial when the sensitizers with low molar extinction coefficients, such as N719, are introduced in the device.